2016
DOI: 10.3168/jds.2015-9925
|View full text |Cite
|
Sign up to set email alerts
|

Imagining the ideal dairy farm

Abstract: Practices in agriculture can have negative effects on the environment, rural communities, food safety, and animal welfare. Although disagreements are possible about specific issues and potential solutions, it is widely recognized that public input is needed in the development of socially sustainable agriculture systems. The aim of this study was to assess the views of people not affiliated with the dairy industry on what they perceived to be the ideal dairy farm and their associated reasons. Through an online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
138
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(163 citation statements)
references
References 40 publications
14
138
0
6
Order By: Relevance
“…Although some of these approaches may differ from what the public imagines as ideal (i.e. that cows are on pasture all the time; Cardoso et al 2016), we have found that people are often receptive to these hybrid solutions when the constraints and context is provided (e.g. that cows often prefer to come inside during the day and escape the hot sun, and that allowing cows to use pasture when the soil is too wet can damage the pasture).…”
Section: Engage With the Publicmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some of these approaches may differ from what the public imagines as ideal (i.e. that cows are on pasture all the time; Cardoso et al 2016), we have found that people are often receptive to these hybrid solutions when the constraints and context is provided (e.g. that cows often prefer to come inside during the day and escape the hot sun, and that allowing cows to use pasture when the soil is too wet can damage the pasture).…”
Section: Engage With the Publicmentioning
confidence: 99%
“…People expect, at a minimum, humane care, appropriate hygiene and good husbandry (Cardoso et al 2016), but how can the dairy industry prove that it lives up to these minimum standards? In addition, can the dairy industry position itself so that instead of simply responding to welfare concerns as external threats, it develops a vision that positions itself as a leader on welfare issues?…”
Section: Role For Policymentioning
confidence: 99%
See 2 more Smart Citations
“…It considerably affects milk production, animal welfare, and food safety [68]. Today’s consumers make increasing demands for adequate animal welfare as well as food quality and safety, which also must be taken into account on modern dairy farms [9]. …”
Section: Introductionmentioning
confidence: 99%